Relationship between anthropometric characteristics and jump shot skill in female basketball players - Shahdadi, A.; Alisoufi, N. (European Journal of Physical Education and Sport Science, 2016)
The aim of this study was to evaluate the Relationship between anthropometric characteristics and jump shot skill in female basketball players. The statistical population consisted of all adolescent female basketball players in Zahedan. The subjects were included in this study by convenient sampling. 30 teenage female basketball players (15-18 years old) were selected. Measurement of research variables including height, weight, BMI, hip circumference, leg circumference, arm circumference, forearm circumference, hip length, triceps skin fold, under the scapular and biceps fat thickness and jump shot skill were measured using standard tool. For statistical analysis of the data, the Pearson correlation coefficient was used. The results showed a significant relationship between the variables of height (P=0.0001) and BMI (P=0.006) and shot skill score, but the rest of variables showed no statistically significant difference in terms of shot skill score. While a significant relationship between height and BMI and shooting skills was observed, most of the variables had no significant relationship with shot skill and for clarification of the data in this regard, there need to do more research so that by understanding this information in selection of the players and identifying of talents in basketball and training development programs, useful information would be provided to coaches and athletes.